Depoliticisation of the Political: Dealing with Political Issues in Slovenian Dailies - Pikalo, Jernej; Trdina, Andreja (Javnost-The Public, 2009)
The article examines the process of depoliticisation of the political by looking at how political issues have been dealt with in the Slovenian dailies in the period between 1990 and 2005. Depoliticisation is defi ned by parallel processes of neo-liberalism and globalism that share politics of diminishing infl uence of demos on democratic decisions of political communities. Content analysis of Slovenian dailies in the years of 1990, 1995, 2000, and 2005, reveals the following changes towards depoliticisation: Slovenian actors increasingly quote international actors as a reference during that period; international actors quoted by Slovenian actors are increasingly presented as depersonalised; there is a growing consent among Slovenian political sources in quoting privatised economic actors; the decreasing level of expressed disagreements is accompanied by growing personalisation of economic actors.